Multi-objective beamforming for energy-efficient SWIPT systems - Leng, Shiyang; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Schober, Robert (2016 International Conference on Computing, Networking and Communications (ICNC), 2016)
In this paper, we study the resource allocation algorithm design for energy-efficient simultaneous wireless information and power transfer (SWIPT) systems. The considered system comprises a transmitter, an information receiver, and multiple energy harvesting receivers equipped with multiple antennas. We propose a multi-objective optimization framework to study the trade-off between the maximization of the energy efficiency of information transmission and the maximization of wireless power transfer efficiency. The proposed problem formulation takes into account the per antenna circuit power consumption of the transmitter and the imperfect channel state information of the energy harvesting receivers. The adopted non-convex multi-objective optimization problem is transformed into an equivalent rank-constrained semidefinite program (SDP) and optimally solved by SDP relaxation. Numerical results unveil an interesting trade-off between the considered conflicting system design objectives and reveal the benefits of multiple transmit antennas for improving system energy efficiency.<br
Keywords: Receivers; Transmitters; System analysis and design; Resource Management; Energy harvesting; Optimization; Erbium

Multi-Objective Power Allocation for Energy Efficient Wireless Information and Power Transfer Systems - Leng, Shiyang (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Power efficient and secure multiuser communication systems with wireless information and power transfer - Leng, Shiyang; Ng, Derrick Wing Kwan; Schober, Robert (2014 IEEE International Conference on Communications Workshops, ICC 2014, 2014)
In this paper, we study resource allocation algorithm design for power efficient secure communication with simultaneous wireless information and power transfer (WIPT) in multiuser communication systems. In particular, we focus on power splitting receivers which are able to harvest energy and decode information from the received signals. The considered problem is modeled as an optimization problem which takes into account a minimum required signal-to-interference-plus-noise ratio (SINR) at multiple desired receivers, a maximum tolerable data rate at multiple multi-antenna potential eavesdroppers, and a minimum required power delivered to the receivers. The proposed problem formulation facilitates the dual use of artificial noise in providing efficient energy transfer and guaranteeing secure communication. We aim at minimizing the total transmit power by jointly optimizing transmit beamforming vectors, power splitting ratios at the desired receivers, and the covariance of the artificial noise. The resulting non-convex optimization problem is transformed into a semidefinite programming (SDP) and solved by SDP relaxation. We show that the adopted SDP relaxation is tight and achieves the global optimum of the original problem. Simulation results illustrate the significant power saving obtained by the proposed optimal algorithm compared to suboptimal baseline schemes. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03